Polyamide material for light high-strength safety airbag shell and preparation method of polyamide material

By phosphating the potassium hexattitanate whiskers and combining with carboxylated lignin and silk fibroin, a crosslinking network structure is formed, which solves the water absorption and compatibility of polyamide materials, and improves its mechanical strength and Impact energy absorption performance, suitable for lightweight, high-strength airbag housing materials.

CN119242037AInactive Publication Date: 2025-01-03NANJING YUEBEIST NEW MATERIALS TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411775631.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The amide groups in the polyamide molecular chain easily form hydrogen bonds with the water molecules in the environment, resulting in poor performance of the polyamide material, and poor compatibility with the metal organic frame and the polyamide material, affecting its machinery. Performance and wear resistance.

Method used

Potassium hexattitanate whiskers are phosphated by phosphoric acid to form a uniformly dispersed metal organic framework, and combine with carboxylated lignin and silk fibroin to form a crosslinking network structure, introduce hydrophobic groups, and improve the polyamide material Toughness and strength, while modified potassium hexatitate whiskers are embedded in the crosslinking network structure to enhance its dispersion stability.

Benefits of technology

It significantly improves the mechanical strength, wear resistance and impact energy absorption performance of polyamide materials, reduces water absorption, enhances the thermal stability and toughness of the material, effectively reduces friction and thermoplastic deformation, and improves the performance of the airbag shell .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a polyamide material for a light high-strength safety airbag shell and a preparation method of the polyamide material, and belongs to the technical field of modified polyamide materials. Comprising the following raw materials in parts by mass: 80-120 parts of modified polyamide resin, 10-15 parts of carboxylated lignin, 5-10 parts of modified potassium hexatitanate whiskers, 4-5 parts of silk fibroin, 1-2 parts of an antioxidant, 1-1.4 parts of a coupling agent, 1-1.5 parts of a lubricant, 0.5-0.9 part of a nucleating agent and 60-80 parts of deionized water. The potassium hexatitanate whisker is used as a carrier of the zinc-based metal organic framework, so that the impact resistance of the zinc-based metal organic framework is improved, the impact energy required by hole collapse and zinc-nitrogen bond breakage of the zinc-based metal organic framework is increased, and the injury to personnel caused by larger impact force when the safety airbag is started to pop off a polyamide shell material is avoided; the cucurbit [6] uril is grafted on a polyamide molecular chain, and a hydrophobic group is introduced on the polyamide molecular chain, so that the water absorption of the polyamide resin is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified polyamide materials, in particular to a light-weight and high-strength polyamide material for a safety airbag housing and a preparation method thereof. Background Art

[0002] As a thermoplastic material, polyamide exhibits relatively low density, good mechanical strength, heat resistance, chemical resistance to grease and solvent media, durability, resistance to stress cracking and aging. It is usually used in automotive parts, sporting goods, aircraft and other high-performance materials. Because it can withstand high loads of fillers, polyamide is used as an airbag shell material with the characteristics of light weight and high strength. By adding fillers with different structures to increase the flexibility, impact resistance and wear resistance of polyamide materials, polyamide materials are widely used in the field of airbag shell materials.

[0003] As an airbag shell material, polyamide has the advantages of light weight, high strength and good corrosion resistance. However, the amide groups in the polyamide molecular chain easily form hydrogen bonds with water molecules in the environment and have a large water absorption rate, resulting in poor performance of the polyamide material. Adding potassium hexatitanate whiskers and metal-organic frameworks to polyamide materials can improve the mechanical properties and wear resistance of polyamide materials, but potassium hexatitanate whiskers and metal-organic frameworks have poor compatibility with polyamide materials. Summary of the invention

[0004] The object of the present invention is to provide a lightweight and high-strength polyamide material for a safety airbag shell and a preparation method thereof: after potassium hexatitanate whiskers are phosphated with phosphoric acid, they are mixed with imidazole monomers and a zinc source for reaction, and phosphoric acid is coated on the surface of the potassium hexatitanate whiskers, so that the potassium hexatitanate whiskers have high surface activity and can form a uniformly dispersed metal organic framework on the surface of the pretreated potassium hexatitanate whiskers. The potassium hexatitanate whiskers, as carriers of the zinc-based metal organic framework, have an excellent aspect ratio, can absorb stress, and increase the impact energy required for the collapse of the zinc-based metal organic framework holes and the breaking of the zinc-nitrogen bond; cucurbitac[6]uril is oxidized with an oxidant, and then reacted with an amino acid. The monomer is reacted to form a dibasic acid structure, and the dibasic acid and diamine undergo an amine copolymerization reaction to graft the cucurbitacin[6]urea macrocyclic molecular structure in the monomer onto the polyamide molecular chain; the monomer, dibasic acid, diamine, and solvent are mixed and amine copolymerization is performed, and then the cucurbitacin[6]urea macrocyclic molecular structure in the monomer is grafted onto the polyamide molecular chain by reducing pressure, evacuating, and discharging the material, thereby introducing a hydrophobic group and reducing the water absorption of the polyamide resin; the polyamide material also includes a cross-linked network structure formed by carboxylated lignin and silk fibroin, and the modified potassium hexatitanate whisker is embedded in the cross-linked network structure, thereby improving the dispersion stability of the modified potassium hexatitanate whisker in the polyamide material.

[0005] The technical problem to be solved by the present invention is that the amide groups in the polyamide molecular chain easily form hydrogen bonds with water molecules in the environment, have a large water absorption rate, and result in poor performance of the polyamide material; adding potassium hexatitanate whiskers and metal organic frameworks to the polyamide material can improve the mechanical properties and wear resistance of the polyamide material, but the compatibility of potassium hexatitanate whiskers and metal organic frameworks with the polyamide material is poor.

[0006] To achieve the above object, the present invention provides the following technical solutions: A light and high-strength polyamide material for an airbag shell comprises the following raw materials in parts by weight: 80-120 parts of modified polyamide resin, 20-30 parts of carboxylated lignin, 5-10 parts of modified potassium hexatitanate whiskers, 4-5 parts of silk fibroin, 1-2 parts of an antioxidant, 1-1.4 parts of a coupling agent, 1-1.5 parts of a lubricant, 0.5-0.9 parts of a nucleating agent, and 60-80 parts of deionized water.

[0007] A method for preparing a lightweight and high-strength polyamide material for an airbag housing comprises the following steps: S1. Add carboxylated lignin, modified potassium hexatitanate whiskers, and silk fibroin into deionized water, stir at 40-60° C. for 1-2 h, and filter to obtain a solid.

[0008] Among them, the amino and hydroxyl groups on the silk fibroin molecular chain can react with the carboxyl groups in the carboxylated lignin, and combine through amide bonds and ester groups to form a cross-linked network structure, thereby improving the toughness and strength of the polyamide material. The modified potassium hexatitanate whiskers are embedded in the cross-linked network structure, thereby improving the dispersion stability of the modified potassium hexatitanate whiskers in the polyamide material. In addition, the amide bonds and ester groups introduced into the cross-linked network structure can combine with polyamide through hydrogen bonds, thereby increasing the binding force between the modified potassium hexatitanate whiskers and the polyamide material.

[0009] S2. The modified polyamide, solid, coupling agent, antioxidant, lubricant and nucleating agent are mixed, placed in a mixer, stirred evenly, placed in a twin-screw extruder for extrusion and granulation to obtain a polyamide material.

[0010] Furthermore, the antioxidant is selected from any one of 1010 antioxidant, 168 antioxidant, 1098 antioxidant, 1076 antioxidant, H10 antioxidant, and H161 antioxidant.

[0011] Furthermore, the coupling agent is selected from any one of isopropyl triisostearate titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate, vinyl tri(β-methoxyethoxy) silane, γ-methacryloxypropyl trimethoxy silane, and bis(dioctylpyrophosphate)ethylene titanate.

[0012] Furthermore, the nucleating agent is selected from any one of kaolin, montmorillonite, clay and talc.

[0013] Furthermore, the lubricant is selected from any one of polyethylene wax, silicone, zinc stearate, and calcium stearate.

[0014] Furthermore, the temperature of zone 1 of the twin-screw extruder is 90-150°C, the temperature of zone 2 is 220-260°C, the temperature of zone 3 is 220-260°C, the temperature of zone 4 is 220-260°C, the temperature of zone 5 is 230-260°C, the temperature of zone 6 is 230-260°C, the temperature of zone 7 is 230-260°C, the temperature of zone 8 is 230-260°C, and the temperature of zone 9 is 220-250°C.

[0015] Furthermore, the rotation speed of the twin-screw extruder is 250-300 r / min.

[0016] Further, the carboxylated lignin is specifically prepared by the following steps: Add lignin to deionized water, add a 6.25 mol / L sodium hydroxide aqueous solution, stir evenly, heat to 60°C, add sodium chloroacetate, stir to react for 2 hours, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 70°C for 10 minutes to obtain carboxylated lignin.

[0017] Among them, under alkaline conditions (provided by a sodium hydroxide aqueous solution with a concentration of 6.25 mol / L), the carbon in the sodium chloroacetate molecule will be attacked, resulting in the removal of chlorine atoms, and combining with the alcoholic hydroxyl and phenolic hydroxyl groups on the lignin through chemical bonds, thereby introducing carboxymethyl groups on the lignin molecules to form carboxylated lignin.

[0018] Furthermore, the dosage ratio of lignin, deionized water, sodium hydroxide aqueous solution, and sodium chloroacetate is (1-2) g: (20-30) mL: (6-10) mL: (0.3-0.7) g.

[0019] Furthermore, the modified potassium hexatitanate whisker is prepared by phosphating the potassium hexatitanate whisker with phosphoric acid and then reacting the mixture with imidazole monomer and zinc source.

[0020] Furthermore, the imidazole monomer is selected from 2-methylimidazole or 4-methylimidazole.

[0021] Furthermore, the zinc source is selected from zinc nitrate hexahydrate or zinc acetate dihydrate.

[0022] Furthermore, the potassium hexatitanate whisker has a diameter of 50-100 nm and a length of 5-10 μm.

[0023] Furthermore, the modified potassium hexatitanate whiskers are prepared by the following steps: A1. Add potassium hexatitanate whiskers and 2.5% isopropanol aqueous solution to 0.5% phosphoric acid aqueous solution, stir for 10 minutes, heat treat at 80°C for 1 hour, then heat treat at 120°C for 2.5 hours, cool to room temperature, filter, wash with deionized water for 3 times, and dry in an oven at 80°C for 8 minutes to obtain pretreated potassium hexatitanate whiskers.

[0024] Among them, the surface of potassium hexatitanate whiskers contains a large number of titanium-oxygen bonds and hydroxyl structures, which can be chemically bonded with the phosphorus hydroxyl groups in phosphoric acid, so that the phosphoric acid is coated on the surface of the potassium hexatitanate whiskers, thereby improving the surface activity of the potassium hexatitanate whiskers and serving as a binding site for the metal organic framework.

[0025] Furthermore, the dosage ratio of potassium hexatitanate whisker, isopropanol aqueous solution, and phosphoric acid aqueous solution is (1-2) g: (8-12) mL: (45-55) mL.

[0026] A2. Add imidazole monomer to deionized water, stir until completely dissolved, add zinc source and pretreated potassium hexatitanate whiskers, stir at 25°C for 24 hours to obtain a suspension, centrifuge the suspension at 2500 rpm, wash 3 times with methanol, wash 3 times with deionized water, and dry in an oven at 70°C for 15 minutes to obtain modified potassium hexatitanate whiskers.

[0027] Among them, the phosphorus hydroxyl groups contained on the surface of the pretreated potassium hexatitanate whiskers can combine with zinc ions in the zinc source zinc nitrate hexahydrate, so that the zinc ions are adsorbed on the surface of the potassium hexatitanate whiskers, and the zinc ions can react with the nitrogen atoms in the imidazole monomer 2-methylimidazole to form a nitrogen-zinc bond complex on the surface of the pretreated potassium hexatitanate whiskers. As the coordination reaction proceeds, nitrogen-zinc coordination bonds are continuously formed between the zinc ions and the 2-methylimidazole molecules. These coordination bonds connect the Zn ions and the 2-methylimidazole molecules together, thereby forming a porous zinc-based metal organic framework on the surface of the pretreated potassium hexatitanate whiskers.

[0028] Furthermore, the dosage ratio of imidazole monomer, deionized water, zinc source, and pretreated potassium hexatitanate whiskers is (12-12.6) g: (90-110) mL: (0.7-0.8) g: (2-2.6) g.

[0029] Furthermore, the modified polyamide resin is prepared by mixing monomers, dibasic acid, diamine and solvent, copolymerizing with amine, and then vacuumizing and discharging the mixture under reduced pressure.

[0030] Furthermore, the dibasic acid is selected from any one of succinic acid, glutaric acid, adipic acid, undecanedioic acid, dodecanedioic acid, and tridecanedioic acid.

[0031] Furthermore, the diamine is selected from any one of pentamethylenediamine, ethylenediamine and hexamethylenediamine.

[0032] Furthermore, the solvent is selected from toluene or xylene.

[0033] Furthermore, the specific operation of reducing pressure, vacuumizing and discharging is as follows: vacuumizing at 200-240° C. to a pressure of 1.2-1.3 KPa, maintaining for 0.5-1 h, cooling to 170-190° C., and discharging.

[0034] Further, the modified polyamide resin is specifically prepared by the following steps: The monomer and the dibasic acid are added to the solvent, stirred at 110°C for 15 minutes to obtain a mixed solution, the diamine is added to the deionized water, stirred evenly, added to the mixed solution, copolymerized at 110°C for 45 minutes, heated to 155°C, stirred for 15 minutes, and continued to heat to 230°C. After keeping the temperature for 2 hours, the pressure is reduced and vacuumed to 1.25 KPa. After maintaining the pressure for 30 minutes, the temperature is lowered to 180°C, the material is discharged, and cooled to room temperature to obtain a modified polyamide resin.

[0035] The carboxyl group carried by the glutamic acid in the monomer as a dibasic acid component undergoes copolymerization reaction with the dibasic acid and the diamine to form a polyamide resin, thereby grafting the cucurbitacin[6]uril macrocyclic molecular structure in the monomer onto the polyamide molecular chain. The cavity structure of cucurbitacin[6]uril in the monomer has excellent hydrophobic properties, and hydrophobic groups are introduced into the polyamide molecular chain, thereby reducing the water absorption of the polyamide resin.

[0036] Furthermore, the usage ratio of monomer, dibasic acid, solvent, diamine and deionized water is (1-2) g: (2-3) g: (45-55) mL: (2-2.2) g: (15-25) mL.

[0037] Furthermore, the monomer is obtained by oxidizing cucurbit[6]uril with an oxidant and then reacting with an amino acid.

[0038] Furthermore, the oxidant is prepared by mixing ferrous chloride and hydrogen peroxide in a ratio of (0.2-0.3) g: (15-20) mL. Furthermore, the amino acid is selected from any one of glycine, alanine and lysine.

[0039] Further, the monomer is specifically prepared by the following steps: Add cucurbitacin[6]uril to a 36% by mass aqueous solution of hydrochloric acid, stir evenly, add an oxidant, stir and react for 1 hour, centrifuge to obtain a precipitate, dry the precipitate in an oven at 70°C for 10 minutes to obtain hydroxycucurbitacin[6]uril, add hydroxycucurbitacin[6]uril and amino acid to deionized water, stir evenly, add a 2 mol / L aqueous solution of sodium hydroxide, stir and react for 2 hours, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 20 minutes to obtain a monomer.

[0040] Among them, ferrous chloride and hydrogen peroxide are used as oxidants. The ferrous ions and hydrogen peroxide provided can stimulate the generation of hydroxyl radicals. The generated hydroxyl radicals can undergo substitution reactions with the hydrogen atoms in cucurbit[6]uril, so that the surface of cucurbit[6]uril carries a large number of hydroxyl groups and has excellent reaction activity, thus forming hydroxycucurbit[6]uril.

[0041] Furthermore, an aqueous sodium hydroxide solution is used as a catalyst to react the hydroxyl group of hydroxycucurbit[6]uril with the amino group of the amino acid, so that the amino acid is grafted onto the hydroxycucurbit[6]uril to form a monomer.

[0042] Furthermore, the mass ratio of cucurbit[6]uril to oxidant is (2-3):(0.3-0.7).

[0043] Furthermore, the dosage ratio of hydroxycucurbit[6]uril, amino acid, deionized water, and sodium hydroxide aqueous solution is (1-2) g:(10-20) g:(180-220) mL:(2.6-3) mL.

[0044] Furthermore, compared with the prior art, the present invention has the following beneficial effects: (1) In the technical solution of the present invention, potassium hexatitanate whiskers have excellent load-bearing capacity. During the friction process, the whiskers partially replace the polyamide resin to carry the load, reducing friction and preventing the thermoplastic deformation of the polyamide material, thereby effectively improving the wear resistance of the polyamide material. Phosphoric acid is coated on the surface of the potassium hexatitanate whiskers, and the pretreated potassium hexatitanate whiskers formed have high surface activity and can form a uniformly dispersed metal organic framework on the surface of the pretreated potassium hexatitanate whiskers. A porous zinc-based metal organic framework is formed on the surface of the pretreated potassium hexatitanate whiskers. The synthesized metal organic framework shows the potential for mechanical energy attenuation. When the airbag is hit by an external force, the pores and zinc-nitrogen bonds in the zinc-based metal organic framework can absorb the impact energy generated by the external force, and the pores of the metal-organic framework collapse and the zinc-nitrogen bonds break, thereby dissipating the shock wave, consuming the impact energy generated by the external force, effectively absorbing the impact energy, and reducing the damage to passengers caused by the collision.

[0045] (2) In the technical solution of the present invention, potassium hexatitanate whiskers as carriers of zinc-based metal organic frameworks have an excellent aspect ratio, can absorb stress, improve the impact resistance of the zinc-based metal organic framework, and increase the impact energy required for the collapse of zinc-based metal organic framework pores and the breaking of zinc-nitrogen bonds, thereby avoiding the large impact force when the airbag is activated and the polyamide shell material is ejected to cause harm to personnel; the modified potassium hexatitanate whiskers are filled in the polyamide material and are confined in the polyamide molecular structure, thereby reducing the movement of the polyamide molecular chain, improving the crystallinity of the polyamide material during the melting process, and thereby enhancing the thermal stability and mechanical strength of the polyamide material.

[0046] (3) In the technical scheme of the present invention, carboxylated lignin and silk fibroin are combined through amide bonds and ester groups to form a cross-linked network structure, thereby improving the toughness and strength of the polyamide material, and the modified potassium hexatitanate whiskers are embedded in the cross-linked network structure, thereby improving the dispersion stability of the modified potassium hexatitanate whiskers in the polyamide material. In addition, the amide bonds and ester groups introduced into the cross-linked network structure can combine with polyamide through hydrogen bonds, thereby increasing the binding force between the modified potassium hexatitanate whiskers and the polyamide material, and the silk fibroin has excellent toughness, thereby ensuring that the finally prepared polyamide material has higher toughness and strength.

[0047] (4) In the technical scheme of the present invention, hydroxycucurbit[6]uril reacts with amino acid to graft amino acid onto hydroxycucurbit[6]uril to form a monomer as a dibasic acid structure, which undergoes amine copolymerization with dibasic acid and diamine to form a polyamide resin, thereby grafting the macrocyclic molecular structure of cucurbit[6]uril in the monomer onto the polyamide molecular chain. The cavity structure of cucurbit[6]uril in the monomer has excellent hydrophobic properties, and hydrophobic groups are introduced into the polyamide molecular chain, thereby reducing the water absorption of the polyamide resin. In addition, the macrocyclic rigid structure contained in cucurbit[6]uril has good stability and mechanical strength, thereby improving the mechanical strength of the polyamide material. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The raw materials used in the examples of the present invention are as follows: lignin (purchased from Hunan Yongzhou Xiangjiang Paper Co., Ltd.); sodium chloroacetate (purity of 99.9%, model 3926-62-3); silk fibroin (purchased from Shanghai Yuanye Biotechnology Co., Ltd., molecular weight of 2kDa); isopropanol (model 67-63-0, purchased from Jinzhou Petrochemical Company); phosphoric acid (purity of 85%, model 7664-38-2); zinc nitrate hexahydrate (purchased from Shanghai Dingfen Chemical Technology Co., Ltd., purity of 98%) ; 2-methylimidazole (model 551-92-8, purity 99.5%); ferrous chloride, hydrogen peroxide (analytical grade, manufacturer: Tianjin Fengchuan Chemical Reagent Technology Co., Ltd.); cucurbitacin [6] uril (purity 99%, purchased from Hubei Jusheng Technology Co., Ltd.); adipic acid (purity 99.6%, model 124-04-9); pentamethylenediamine (purity 98%, Hubei Zhenbo Chemical Co., Ltd.); potassium hexatitanate whiskers (model 12030-97-6, true specific gravity 3.2 g / cm 3 , purity is 95.6%, softening point temperature is 1200℃).

[0050] Example 1 The modified potassium hexatitanate whiskers are prepared by the following steps: A1. Add 1.5 g potassium hexatitanate whiskers and 10 mL of 2.5% isopropanol aqueous solution to 50 mL of 0.5% phosphoric acid aqueous solution, stir for 10 min, heat treat at 80 ° C for 1 h, then heat treat at 120 ° C for 2.5 h, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 80 ° C for 8 min to obtain pretreated potassium hexatitanate whiskers.

[0051] A2. Add 12.3 g of 2-methylimidazole to 100 mL of deionized water and stir until completely dissolved. Add 0.75 g of zinc nitrate hexahydrate and 2.3 g of pretreated potassium hexatitanate whiskers and stir at 25°C for 24 h to obtain a suspension. Centrifuge the suspension at 2500 rpm to obtain a precipitate. Wash the precipitate three times with methanol and three times with deionized water, and dry it in an oven at 70°C for 15 min to obtain modified potassium hexatitanate whiskers.

[0052] Comparative Example 1 The difference between this comparative example and Example 1 is that the pretreated potassium hexatitanate whiskers are replaced with potassium hexatitanate whiskers, and the remaining steps and raw materials are the same as Example 1.

[0053] Add 12.3 g of 2-methylimidazole to 100 mL of deionized water and stir until completely dissolved. Add 0.75 g of zinc nitrate hexahydrate and 2.3 g of potassium hexatitanate whiskers and stir at 25°C for 24 hours to obtain a suspension. Centrifuge the suspension at 2500 rpm to obtain a precipitate. Wash the precipitate three times with methanol and three times with deionized water, and dry it in an oven at 70°C for 15 minutes to obtain modified potassium hexatitanate whiskers.

[0054] Comparative Example 2 The difference between this comparative example and Example 1 is that no pre-treated potassium hexatitanate whiskers are added, and the remaining steps and raw materials are the same as Example 1.

[0055] 12.3 g of 2-methylimidazole was added to 100 mL of deionized water and stirred until completely dissolved. 0.75 g of zinc nitrate hexahydrate was added and stirred at 25° C. for 24 h to obtain a suspension. The suspension was centrifuged at 2500 rpm to obtain a precipitate. The precipitate was washed 3 times with methanol and 3 times with deionized water, and dried in an oven at 70° C. for 15 min to obtain a zinc-based metal organic framework.

[0056] Example 2 The modified polyamide resin is prepared by the following steps: B1. Mix 0.25 g of ferrous chloride and 16 mL of hydrogen peroxide to obtain an oxidant, add 2.5 g of cucurbitacin[6]uril into 30 mL of 36% hydrochloric acid aqueous solution, stir evenly, add 0.5 g of oxidant, stir and react for 1 h, centrifuge, and dry in an oven at 70°C for 10 min to obtain hydroxycucurbitacin[6]uril, add 1.4 g of hydroxycucurbitacin[6]uril and 15 g of glycine into 200 mL of deionized water, stir evenly, add 2.8 mL of 2 mol / L sodium hydroxide aqueous solution, stir and react for 2 h, filter, wash with deionized water 3 times, and dry in an oven at 50°C for 20 min to obtain a monomer.

[0057] B2. Add 1.5g monomer and 2.5g adipic acid into 50mL toluene, stir for 15min at 110℃ to obtain a mixed solution, add 2.1g pentamethylenediamine into 20mL deionized water, stir evenly, add into the mixed solution, copolymerize at 110℃ for 45min, heat to 155℃, stir for 15min, continue to heat to 230℃, keep warm for 2h, reduce pressure and evacuate to 1.25KPa, keep for 30min, cool to 180℃, discharge, and cool to room temperature to obtain modified polyamide resin.

[0058] Comparative Example 3 The difference between this comparative example and Example 2 is that no monomer is added, and the remaining steps and raw materials are the same as Example 2.

[0059] Add 2.5 g of adipic acid to 50 mL of toluene, stir at 110° C. for 15 min to obtain a mixed solution, add 2.1 g of pentamethylenediamine to 20 mL of deionized water, stir evenly, add to the mixed solution, copolymerize at 110° C. for 45 min, heat to 155° C., stir for 15 min, continue to heat to 230° C., keep warm for 2 h, reduce the pressure and evacuate to 1.25 KPa, keep for 30 min, cool to 180° C., discharge, and cool to room temperature to obtain a polyamide resin.

[0060] Example 3 Carboxylated lignin is prepared by the following steps: Add 1.75 g of lignin to 25 mL of deionized water, add 8 mL of 6.25 mol / L sodium hydroxide aqueous solution, stir evenly, heat to 60 ° C, add 0.5 g of sodium chloroacetate, stir and react for 2 hours, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 70 ° C for 10 minutes to obtain carboxylated lignin.

[0061] Example 4 A lightweight and high-strength polyamide material for an airbag shell comprises the following raw materials in parts by mass: 80 parts of the modified polyamide resin prepared in Example 2, 20 parts of the carboxylated lignin prepared in Example 3, 5 parts of the modified potassium hexatitanate whiskers prepared in Example 1, 4 parts of silk fibroin, 1 part of 1010 antioxidant, 1 part of isopropyl titanate triisostearate, 1 part of polyethylene wax, 0.5 parts of kaolin, and 60 parts of deionized water.

[0062] A method for preparing a lightweight and high-strength polyamide material for an airbag housing comprises the following steps: S1. The carboxylated lignin prepared in Example 3, the modified potassium hexatitanate whiskers prepared in Example 1, and the silk fibroin were added to deionized water, stirred at 50° C. for 1.5 h, filtered, and dried in an oven at 70° C. for 15 min to obtain a solid; S2. The modified polyamide resin prepared in Example 2, solid, isopropyl titanate triisostearate, 1010 antioxidant, polyethylene wax, and kaolin are mixed, placed in a blender, stirred evenly, placed in a twin-screw extruder for extrusion and granulation to obtain a polyamide material, wherein the temperature of zone 1 of the twin-screw extruder is 125°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 255°C, the temperature of zone 6 is 256°C, the temperature of zone 7 is 250°C, the temperature of zone 8 is 240°C, the temperature of zone 9 is 245°C, and the speed of the twin-screw extruder is 280r / min.

[0063] Example 5 A lightweight and high-strength polyamide material for an airbag shell comprises the following raw materials in parts by mass: 100 parts of the modified polyamide resin prepared in Example 2, 25 parts of the carboxylated lignin prepared in Example 3, 8 parts of the modified potassium hexatitanate whiskers prepared in Example 1, 4.5 parts of silk fibroin, 1.5 parts of 168 antioxidant, 1.2 parts of isopropyl tri(dodecylbenzenesulfonyl) titanate, 1.3 parts of zinc stearate, 0.7 parts of montmorillonite, and 70 parts of deionized water.

[0064] A method for preparing a lightweight and high-strength polyamide material for an airbag housing comprises the following steps: S1. The carboxylated lignin prepared in Example 3, the modified potassium hexatitanate whiskers prepared in Example 1, and the silk fibroin were added to deionized water, stirred at 50° C. for 1.5 h, filtered, and dried in an oven at 70° C. for 15 min to obtain a solid; S2. The modified polyamide resin prepared in Example 2, solid, isopropyl tri(dodecylbenzenesulfonyl) titanate, antioxidant, zinc stearate, and montmorillonite are mixed, placed in a blender, stirred evenly, placed in a twin-screw extruder for extrusion and granulation to obtain a polyamide material, wherein the temperature of zone 1 of the twin-screw extruder is 125°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 255°C, the temperature of zone 6 is 256°C, the temperature of zone 7 is 250°C, the temperature of zone 8 is 240°C, the temperature of zone 9 is 245°C, and the speed of the twin-screw extruder is 280r / min.

[0065] Example 6 A lightweight and high-strength polyamide material for an airbag shell comprises the following raw materials in parts by mass: 120 parts of modified polyamide resin prepared in Example 2, 30 parts of carboxylated lignin prepared in Example 3, 10 parts of modified potassium hexatitanate whiskers prepared in Example 1, 5 parts of silk fibroin, 2 parts of 1098 antioxidant, 1.4 parts of bis(dioctyl pyrophosphate) ethylene titanate, 1.5 parts of calcium stearate, 0.9 parts of clay, and 80 parts of deionized water.

[0066] A method for preparing a lightweight and high-strength polyamide material for an airbag housing comprises the following steps: S1. The carboxylated lignin prepared in Example 3, the modified potassium hexatitanate whiskers prepared in Example 1, and the silk fibroin were added to deionized water, stirred at 50° C. for 1.5 h, filtered, and dried in an oven at 70° C. for 15 min to obtain a solid; S2. The modified polyamide resin prepared in Example 2, solid, bis(dioctyl pyrophosphate)ethylene titanate, 1098 antioxidant, calcium stearate, and clay are mixed, placed in a mixer, stirred evenly, placed in a twin-screw extruder for extrusion and granulation to obtain a polyamide material, wherein the temperature of zone 1 of the twin-screw extruder is 125°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 250°C, the temperature of zone 5 is 255°C, the temperature of zone 6 is 256°C, the temperature of zone 7 is 250°C, the temperature of zone 8 is 240°C, and the temperature of zone 9 is 245°C, and the speed of the twin-screw extruder is 280r / min.

[0067] Comparative Example 4 The difference between this comparative example and Example 5 is that the modified potassium hexatitanate whiskers are replaced by the material prepared in Comparative Example 1, and the remaining steps and raw materials are the same as those in Example 5.

[0068] Comparative Example 5 The difference between this comparative example and Example 5 is that the modified potassium hexatitanate whiskers are replaced by the material prepared in Comparative Example 2, and the remaining steps are synchronized with Example 5.

[0069] Comparative Example 6 The difference between this comparative example and Example 5 is that the modified polyamide resin is replaced by the material prepared in Comparative Example 3, and the remaining steps are synchronized with Example 5.

[0070] Comparative Example 7 The difference between this comparative example and Example 5 is that the carboxylated lignin is replaced by lignin, and the remaining steps are the same as Example 5.

[0071] Comparative Example 8 The difference between this comparative example and Example 5 is that no silk fibroin is added, and the remaining steps are the same as Example 5.

[0072] The performance of the polyamide materials prepared in Examples 4-6 and Comparative Examples 4-8 is now tested.

[0073] The tensile strength of the polyamide material prepared above was tested according to the GB / T1040-2006 standard, with a tensile rate of 10 mm / min; the notched impact strength of the polyamide material prepared above was tested according to the GB / T1043-2008 standard, with the notch type being Type A; the water absorption of the polyamide material prepared above was tested according to the ISO62-2008 standard.

[0074] The heat deformation temperature of the polyamide material prepared above was tested according to the ISO75-2-2013 standard; the wear resistance of the polyamide material prepared above was tested according to the GB / T9867-2008 standard; the test results are shown in Table 1 below:

[0075] The impact energy absorption performance of the polyamide material prepared above was tested according to the IEC60068-2-27 standard. The polyamide material prepared above was placed in an impact compression device, and an impact test was performed under a shock wave energy of 20 KJ / g to detect the shock wave energy after the impact. The test results are shown in Table 2 below:

[0076] It can be seen from the data in Table 1 and Table 2 that in Comparative Example 4, the pretreated potassium hexatitanate whiskers are replaced with potassium hexatitanate whiskers, and the prepared modified potassium hexatitanate whiskers are added to the polyamide material, and the impact energy absorption performance is weakened, and the mechanical properties of the polyamide material are reduced. This may be because phosphoric acid is coated on the surface of the potassium hexatitanate whiskers, and can form a uniformly dispersed metal organic framework on the surface of the pretreated potassium hexatitanate whiskers, thereby improving the mechanical strength of the polyamide material, and the synthesized metal organic framework shows the potential for mechanical energy attenuation; in Comparative Example 5, the zinc-based metal organic framework prepared without adding pretreated potassium hexatitanate whiskers is added to the polyamide material, and its impact energy absorption performance is weakened, and the wear resistance of the polyamide material is reduced. This may be because the potassium hexatitanate whiskers, as a carrier of the zinc-based metal organic framework, have an excellent aspect ratio, can absorb stress, and improve the impact resistance of the zinc-based metal organic framework, and Potassium hexatitanate whiskers have good wear resistance; in Comparative Example 6, a polyamide resin prepared without adding a monomer is used to synthesize a polyamide material, and its water absorption rate increases. This may be because the cavity structure of cucurbitacin [6] uril in the monomer has excellent hydrophobic properties, and hydrophobic groups are introduced into the polyamide molecular chain, thereby reducing the water absorption of the polyamide resin; in Comparative Example 7, a polyamide material prepared by replacing carboxylated lignin with lignin has decreased mechanical strength and energy absorption performance. This may be because carboxylated lignin and silk fibroin are combined through amide bonds and ester groups to form a cross-linked network structure, thereby improving the toughness and strength of the polyamide material and increasing the bonding force between the modified potassium hexatitanate whiskers and the polyamide material; in Comparative Example 8, a polyamide material prepared without adding silk fibroin has decreased toughness. This may be because silk fibroin has excellent toughness, ensuring that the final prepared polyamide material has higher toughness and strength.

[0077] The data in Table 1 and Table 2 show that the polyamide materials prepared in Examples 4-6 not only have good mechanical strength and low water absorption, but also can effectively absorb impact energy as airbag shell materials, reducing the damage to passengers caused by collisions. Carboxylated lignin, modified potassium hexatitanate whiskers, and silk fibroin are added to deionized water, stirred at 40-60°C for 1-2h, filtered, and solids are obtained; modified polyamide, solids, coupling agents, antioxidants, lubricants, and nucleating agents are mixed, placed in a blender, stirred evenly, placed in a twin-screw extruder for extrusion and granulation, and the obtained polyamide materials meet the test performance requirements, while the polyamide materials prepared in Comparative Examples 4-8 do not meet the performance requirements, indicating that the polyamide materials prepared in the present invention not only have good mechanical strength and low water absorption, but also can effectively absorb impact energy as airbag shell materials, reducing the damage to passengers caused by collisions.

[0078] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0079] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A lightweight and high-strength polyamide material for an airbag housing, characterized in that: The invention comprises the following raw materials in parts by weight: 80-120 parts of modified polyamide resin, 10-15 parts of carboxylated lignin, 5-10 parts of modified potassium hexatitanate whiskers, 4-5 parts of silk fibroin, 1-2 parts of antioxidant, 1-1.4 parts of coupling agent, 1-1.5 parts of lubricant, 0.5-0.9 parts of nucleating agent and 60-80 parts of deionized water; The modified potassium hexatitanate whisker is prepared by phosphating the potassium hexatitanate whisker with phosphoric acid and then reacting the mixture with imidazole monomer and zinc source; The modified polyamide resin is prepared by mixing monomers, dibasic acid, diamine and solvent, adding amine for copolymerization, and then reducing pressure, evacuating and discharging. The monomer is prepared by oxidizing cucurbit[6]uril with an oxidant and then reacting with an amino acid.

2. The lightweight and high-strength polyamide material for airbag housing according to claim 1, characterized in that: The imidazole monomer is selected from 2-methylimidazole or 4-methylimidazole; the zinc source is selected from zinc nitrate hexahydrate or zinc acetate dihydrate.

3. The lightweight and high-strength polyamide material for airbag housing according to claim 1, characterized in that: The dibasic acid is selected from any one of succinic acid, glutaric acid, adipic acid, undecanedioic acid, dodecanedioic acid, and tridecanedioic acid; the diamine is selected from any one of ethylenediamine, pentamethylenediamine, and hexamethylenediamine; and the solvent is selected from toluene or xylene.

4. The lightweight and high-strength polyamide material for airbag housing according to claim 1, characterized in that: The specific operation of the reduced pressure vacuuming and discharging is: vacuuming to a pressure of 1.2-1.3 KPa at 200-240° C., maintaining for 0.5-1 h, cooling to 170-190° C., and discharging.

5. The lightweight and high-strength polyamide material for airbag housing according to claim 1, characterized in that: The oxidant is prepared by mixing ferrous chloride and hydrogen peroxide in a dosage ratio of (0.2-0.3) g:(15-20) mL; and the amino acid is selected from any one of glycine, alanine and lysine.

6. The lightweight and high-strength polyamide material for airbag housing according to claim 1, characterized in that: The antioxidant is selected from any one of 1010 antioxidant, 168 antioxidant, 1098 antioxidant, 1076 antioxidant, H10 antioxidant, and H161 antioxidant; the coupling agent is selected from any one of triisostearate isopropyl titanate, isopropyl tri(dodecylbenzenesulfonyl) titanate, vinyl tri(β-methoxyethoxy) silane, γ-methacryloxypropyl trimethoxy silane, and bis(dioctyl pyrophosphate) ethylene titanate.

7. The lightweight and high-strength polyamide material for airbag housing according to claim 1, characterized in that: The nucleating agent is selected from any one of kaolin, montmorillonite, clay and talc; the lubricant is selected from any one of polyethylene wax, silicone, zinc stearate and calcium stearate.

8. A method for preparing a lightweight and high-strength polyamide material for an airbag housing as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Add carboxylated lignin, modified potassium hexatitanate whiskers, and silk fibroin into deionized water, stir at 40-60° C. for 1-2 h, and filter to obtain a solid; S2. The modified polyamide, solid, coupling agent, antioxidant, lubricant and nucleating agent are mixed, placed in a mixer, stirred evenly, placed in a twin-screw extruder for extrusion and granulation to obtain a polyamide material.

9. The method for preparing a lightweight and high-strength polyamide material for an airbag housing according to claim 8, characterized in that: In the step S2, the temperature of the twin-screw extruder zone 1 is 90-150°C, the temperature of zone 2 is 220-260°C, the temperature of zone 3 is 220-260°C, the temperature of zone 4 is 220-260°C, the temperature of zone 5 is 230-260°C, the temperature of zone 6 is 230-260°C, the temperature of zone 7 is 230-260°C, the temperature of zone 8 is 230-260°C, and the temperature of zone 9 is 220-250°C.

10. The method for preparing a light-weight and high-strength polyamide material for an airbag housing according to claim 8, characterized in that: The rotation speed of the twin-screw extruder is 250-300r / min.

Citation Information

Patent Citations

  • Method for synthesizing hydroxycucurbituril by ozone oxidation

    CN113072557A

  • Potassium hexatitanate whisker having tunnel structure

    JP1993000899A

  • Hydroxycucurbituril derivatives, their preparation methods and uses

    US20050075498A1

  • Potassium hexatitanate whiskers having a tunnel structure

    US5366816A

  • High-strength and easy-to-electroplate polyamide composite material and preparation method therefor

    WO2019127417A1